Structural and magnetic characterization of tetranuclear [Ni(II)2Ln(III)2] complexes bearing tetra-branched Schiff base ligands. (15th January 2022) - Shen, Lingyi; Hu, Peng; Yang, Xian-Jiong; Xu, Hong; Huang, Ya-Li; Redshaw, Carl; Zhang, Qi-Long
Graphical abstract: A family of linear Ni(II)2 Ln(III)2 complexes have been successfully prepared based on a tetra-branched Schiff base ligand set. The Dy derivative displayed slow magnetic relaxation under a zero-dc field, and significant magnetocaloric effects for the Gd analogues are found in the low temperature region. Abstract: A series of tetranuclear [Ni(II)2 Ln(III)2 ] complexes of general formula [Ni2 Ln2 (L )(H2 O)9 (OH)4 Cl]∙3H2 O∙Cl (1, 2, 5 ) (Ln = Dy (1 ), Tb (2 ), Ho (5 )) and [Ni2 Ln2 (L )(H2 O)12 Cl] ∙3H2 O∙5Cl (3, 4, 6, 7 ) (Ln = Gd (3 ), Sm (4 ), Nd (6 ), Pr (7 )); H4 L = N, N ', N '', N '''-tetra(3-methoxysalicylidene)-pentaerythritol) have been synthesized. The molecular structures and magnetic properties of 1 –7 are reported. Structural analysis indicated that this family of clusters consists of a tetranuclear [Ni(II)2 Ln(III)2 ] core, supported by a tetrapodal Schiff base ligand. Both Ni(II) ions adopt a distorted octahedral coordination environment, whilst the two terminal Ln(III) ions exhibit distorted tricapped trigonal prismatic geometries and are coordinated by eight or nine oxygen donor atoms. Magnetic measurements revealed that the Dy derivative of complex 1 displays typical d single-molecule magnet behaviour with the presence of slow magnetic relaxation. By contrast, complexes 2 –7, no obvious SMM behaviour was exhibited, however for the Gd derivative 3, a significant magnetocaloric effect was observed.